PkM MESIN PENGIRIS KERIPIK TEMPE BAGI PENGRAJIN OLAHAN TEMPE DI DUSUN CUNGFO - Eko Yudo; Ariyanto Ariyanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Tempe chips are processed snacks made from tempeh-based ingredients. Therefore, it can support the development of activities in the snack food home business sector, one of which is the flagship product,